REGULASI MEKANISME PENGELOLAAN SAMPAH MELALUI BANK SAMPAH DI KOTA PADANG - Hakim, Arif Rahman; Frinaldi, Aldri; Rembrandt, Rembrandt; Lanin, Dasman; Umar, Genius (Al-Isyraq: Jurnal Bimbingan, Penyuluhan, dan Konseling Islam, 2025)
Waste is the remains of human or animal activities that no longer have any use value, and according to the Law on Waste Management, waste can be organic or inorganic. Inorganic waste, especially from industry, takes a long time to decompose, while organic waste such as food waste and plant waste can be recycled biologically. In Indonesia, low public awareness in disposing of waste properly has a negative impact on the environment, such as soil, water, and air pollution. In Padang City, with rapid population growth, the daily volume of waste reaches tens of tons. One solution implemented is the waste bank system, which is a collective mechanism for managing dry waste that encourages people to sort, collect, and recycle waste so that it has economic value and reduces the burden on landfills. Regulatory support provides clear operational guidelines for this system. Research using the Systematic Literature Review (SLR) method shows that the implementation of the waste bank system has increased public awareness and participation through the 3R mechanism (Reduce, Reuse, Recycle), reduced the volume of waste in landfills, and opened up new economic opportunities. However, challenges such as low awareness and limited facilities still need to be overcome through periodic socialization and evaluation, with synergy between the government, waste bank managers, and the community as the key to sustainable waste management and supporting a circular economy.